Hospitalization of patients with acute exacerbation of chronic obstructive pulmonary diseases in Sarapee Hospital: A retrospective study of prevalence and associated factors - Intuvanich, Su-thitaya; Angkurawaranon, Chaisiri; Pinyopornpanish, Kanokporn (Biomedical Sciences and Clinical Medicine, 2018)
Objective To determine the prevalence of hospitalization of patients with acute exacerbation of chronic obstructive pulmonary diseases (AECOPD) and the association with COPD severity, co-morbidities, and treatment options. Methods A retrospective study was conducted with 277 acute exacerbation COPD patients who were diagnosed and treated at Sarapee Hospital between October 2015 and September 2016. The primary outcome was the hospitalization due to acute exacerbation during the year of study. Results Among the AECOPD patients treated at Sarapee Hospital, 21.3% were hospitalized. Predictors of the severity of the disease associated with hospitalization were found to including GOLD (Global Initiative for Obstructive Lung Disease) grade, steroid use, and home oxygen use. Of these three factors, home oxygen therapy was the strongest predictor (aOR=21.61, 95% CI=8.92- 52.38, p<0.001). Patients with ischemic heart disease (IHD) tended to have a higher rate of hospitalization for AECOPD than those with other co-morbidities (aOR=2.59, 95% CI=0.89-7.51, p-value 0.078). We found no statistically significant correlation with the other variables tested. Conclusion Hospitalization for AECOPD was associated with home oxygen use and tended to be associated with IHD. Awareness of means of prevention of disease progression, including proper treatment and comorbid disease control, could potentially decrease the prevalence of hospitalization for AECOPD. Proper use of home oxygen should be further investigated.